Characterization of a microSilicon diode detector for small-field photon beam dosimetry. (25th March 2020) - Akino, Yuichi; Fujiwara, Masateru; Okamura, Keita; Shiomi, Hiroya; Mizuno, Hirokazu; Isohashi, Fumiaki; Suzuki, Osamu; Seo, Yuji; Tamari, Keisuke; Ogawa, Kazuhiko
Abstract: This study characterized a new unshielded diode detector, the microSilicon (model 60023), for small-field photon beam dosimetry by evaluating the photon beams generated by a TrueBeam STx and a CyberKnife. Temperature dependence was evaluated by irradiating photons and increasing the water temperature from 11.5 to 31.3°C. For Diode E, microSilicon, microDiamond and EDGE detectors, dose linearity, dose rate dependence, energy dependence, percent-depth-dose (PDD), beam profiles and detector output factor ( OF det ) were evaluated. The OF det of the microSilicon detector was compared to the field output factors of the other detectors. The microSilicon exhibited small temperature dependence within 0.4%, although the Diode E showed a linear variation with a ratio of 0.26%/°C. The Diode E and EDGE detectors showed positive correlations between the detector reading and dose rate, whereas the microSilicon showed a stable response within 0.11%. The Diode E and microSilicon demonstrated negative correlations with the beam energy. The OF det of microSilicon was the smallest among all the detectors. The maximum differences between the OF det of microSilicon and the field output factors of microDiamond were 2.3 and 1.6% for 5 × 5 mm 2 TrueBeam and 5 mm φ CyberKnife beams, respectively. The PDD data exhibited small variations in the dose fall-off region. The microSilicon and microDiamond detectors yielded similar penumbra widths, whereas the other detectors showed steeper penumbra profiles. The microSilicon demonstrated favorable characteristics including small temperature and dose rate dependence as well as the small spatial resolution and output factors suitable for small field dosimetry.